ACTIVATING STUDENTS’ AESTHETIC FEELINGS IN THE PROCESS OF WORKING IN THE LANDSCAPE GENRE - Aslonov Furqat Botirovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the pedagogical and psychological aspects of activating students’ aesthetic feelings through the study of the landscape genre in fine arts education. It discusses the importance of emotional perception, imagination, and visual analysis in developing creative expression and artistic taste among middle school students. The research emphasizes the use of innovative teaching methods such as digital visualization, the “flipped classroom” model, interactive projects, and outdoor painting activities to enhance aesthetic awareness and appreciation of nature’s beauty.